2013
DOI: 10.3168/jds.2013-6745
|View full text |Cite
|
Sign up to set email alerts
|

Short communication: Fractional milking distribution of immunoglobulin G and other constituents in colostrum

Abstract: The provision of quality colostrum with a high concentration of immunoglobulins is critical for newborn calf health. Because first colostrum may be low in overall concentration to effectively reduce the risk of newborn infections, we tested equivalent milking fractions of colostrum for possible IgG differences. The objective of this study was to determine if the fractional composition of colostrum changes during the course of milking with a focus on immunoglobulins. Twenty-four Holstein and Simmental cows were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 15 publications
(25 reference statements)
1
13
1
1
Order By: Relevance
“…In the present study, a strong correlation was observed between the sRID and the ELISA method. In contrast to our findings, Gelsinger, Smith, et al (2015) reported a weaker relationship between a modified ELISA (Bethyl Laboratories, Montgomery, TX, USA); and the protocol described by Vetter et al (2013), and a commercially available sRID assay (Triple J Farms, Bellingham, WA, USA) when measuring colostrum (R 2 = 0.36; P = .01) and plasma IgG concentrations (R 2 = 0.59; P < .01), although these were still significant. The differences observed between these studies may be specific to the particular kits that were used.…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…In the present study, a strong correlation was observed between the sRID and the ELISA method. In contrast to our findings, Gelsinger, Smith, et al (2015) reported a weaker relationship between a modified ELISA (Bethyl Laboratories, Montgomery, TX, USA); and the protocol described by Vetter et al (2013), and a commercially available sRID assay (Triple J Farms, Bellingham, WA, USA) when measuring colostrum (R 2 = 0.36; P = .01) and plasma IgG concentrations (R 2 = 0.59; P < .01), although these were still significant. The differences observed between these studies may be specific to the particular kits that were used.…”
Section: Discussioncontrasting
confidence: 54%
“…Contrastingly, Lee et al (2008) demonstrated a modified ELISA (Bethyl Laboratories, Montgomery, TX, USA); and the protocol described by Vetter et al (2013) to exhibit a good agreement (94%) with a commercially available sRID assay (Triple J Farms, Bellingham, WA, USA). This may be a consequence of the specific test kits used, as there may be differences between IgG concentrations of standards supplied with kits depending on how they are quantified.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The used ELISA procedure was adapted from the instructions and the protocol described by Vetter et al (2013). Samples of BC and BC fractions for this assay were diluted to get a final concentration of IgG1 in the range between 100 and 500 ng/g.…”
Section: Quantification Of Igg1mentioning
confidence: 99%
“…The composition of BC changes rapidly after parturition. The concentration of IgG in BC can be over 50 g/l (Godden 2008;Vetter et al 2013), while the concentration of IgG in cow's blood serum varies from 2.6 to 38 g/l (Gelsinger et al 2015) and in mature bovine milk its content is in the range of 0.6 g/l to 1 g/l (O'Mahony & Fox 2013).…”
mentioning
confidence: 99%